The potential use of fungi community in postmortem interval estimation in China. (December 2015) - Fu, X.L.; Guo, J.J.; Zhu, Z.Y.; Ding, Z.Y.; Zha, L.; Cai, J.F.
Abstract: Body provides a home for diverse commensal microbiota. Microorganisms such as fungi have major roles in this microbial community stability. Postputrefaction fungi have been recorded in association with decomposed mammalian cadavers in disparate regions. The succession and diversity of these fungi are reviewed with a view to their potential as a forensic tool. The researches of mycology would be an interface to forensic investigation and may provide a means to estimate PMI within serious decomposition. To evaluate the use of succession and diversity of fungi species for PMI estimation, we investigate the Internal Transcribed Spacer (ITS) of fungi community on 3 points of time of rat carcasses conducted by Illumina MiSeq platform. Through high-throughput sequencing, several fungi genus such as Aspergillus, Ophiocordyceps are found in community succession. The community structure of each sample significantly differs in taxon richness and relative abundance patterns within decomposition progress. The succession and diversity of fungi community in corpse decomposition revealed by the indicator of ITS would be a potential forensic tool for PMI estimation.